Regular use of non-steroidal anti-inflammatory drugs can effectively control pain and global health in patients with moderate activity of rheumatoid arthritis - A. E. Karateev; E. Yu. Pogozheva; V. N. Amirdzhanova; E. S. Filatova; V. A. Nesterenko (Современная ревматология)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used to control pain in rheumatoid arthritis (RA). However, many aspects of the therapeutic effect of NSAIDs in RA have not been sufficiently studied. In particular, this concerns the effect of NSAIDs on the inflammatory activity of the disease.Objective: to study the comparative efficacy and safety of NSAIDs in RA patients with moderate and low disease activity.Patients and methods. The study group consisted of 404 patients with RA, 69% women and 31% men, mean age 58.6±10.0 years, with moderate and low disease activity – DAS28<5.1 (mean value 3.7±1.5), who initially had moderate or severe pain: >4 cm on the visual analog scale (VAS) 0–10 cm. All patients received DMARDs, mostly methotrexate 15 to 25 mg weekly, 8.2% biological agents, 18.6% glucocorticoids. All patients were prescribed NSAIDs at the full therapeutic dose. The results of treatment were evaluated after 2 weeks, 1, 3 and 6 months. Criteria of efficacy were the dynamics of pain (10 cm VAS), Patient Global Health (PGH on a 10-cm VAS), the change in the tender joints count (TJC) and swollen joints count(SJC), and dynamics of RA activity (DAS28).Results and discussion. 54.2% of patients received aceclofenac, 19.8% nimesulide, 14.3% meloxicam, 9.1% diclofenac, 2.6% – other NSAIDs. After 2 weeks, the pain decreased from 6.3±1.2 cm to 4.5±1.5 cm on VAS (p<0.001). The severity of pain continued to decrease further, and after 6 months of observation was 4.0±1.2 (p< 001, compared with the baseline level). A similar result was observed for the TJC, SJC, and PGH: the dynamics of these indicators, in comparison with the baseline level, was statistically significant after 2 weeks and after 1, 3, and 6 months of observation (p< 0.05). There was a decrease in the disease activity by DAS28: from 3.7±1.5 to 3.4±1.1 after 3 months (p=0.041) and 3.1±0.9 after 6 months (p=0.02). The effectiveness of aceclofenac and other NSAIDs for pain reduction, TJC, SJC, PGH and DAS28 did not differ. The tolerability of aceclofenac was better than of other NSAIDs: the frequency of dyspepsia after 2 weeks was 23.3% and 36.2% (p=0.004). The frequency of arterial hypertension and edema in patients who used aceclofenac, after 2 weeks and 6 months was slightly lower than in patients treated with other NSAIDs, but the difference was not statistically significant.Conclusion. The use of NSAIDs can effectively control the pain and other symptoms of RA, as well as the disease activity by DAS28 in patients with moderate or low disease activity. Aceclofenac is not inferior to other NSAIDs in analgesic potential and exceeds them in tolerability.